Web and Wireless Geographical Information Systems 8th International Symposium, W2GIS 2008, Shanghai, China, December 11-12, 2008. Proceedings - Bertolotto, Michela; Ray, Cyril; Li, Xiang (Information Systems and Applications, incl. Internet/Web, and HCI, 2008)
This book constitutes the refereed proceedings of the 8th International Symposium on Web and Wirelsss Geographical Information Systems, W2GIS 2008, held in Shanghai, China, in December 2008. The 14 revised full papers presented were carefully reviewed and selected from 38 submissions. The papers span a wide area including but not limited to Conceptual and logical models, Data management and retrieval, Geographical search engines, Web services, Query languages and interfaces, 2D and 3D information visualization, Exploratory cartography and interfaces, Data mining, Security and usability, Location-based services, Peer-to-peer computing, Cyber-geography, Semantic geo-spatial web, Mobile & Wireless GIS, Telematics and GIS Applications, Ubiquitous GIS, Personalization and adaptation as well as Wayfinding and navigation.